Treatment of short bowel syndrome in children. Value of the Intestinal Rehabilitation Program - Tannuri,Uenis (2016)
Summary The main cause of acute intestinal failure is short bowel syndrome, generally as a result of resection of extensive segments of small intestine. As a result, the main symptoms are watery diarrhea, malabsorption syndrome, chronic malnutrition, and death, if the patient is not properly treated. If the length of the remaining intestine is greater than 30 cm, complete adaptation is possible and the patient may not require parenteral nutrition. The currently recommended treatment includes the use of prolonged parenteral nutrition and enteral nutrition, always aimed at constant weight gain, in conjunction with surgeries aimed at elongating the dilated bowel. This set of procedures constitutes what is called an Intestinal Rehabilitation Program. This therapy was used in 16 children in periods ranging from 8 months to 7.5 years, with survival in 75% of the cases. Finally, the last resort to be used in children with complete resection of the small bowel is an intestinal transplant. However, to date there is no record of a Brazilian child that has survived this procedure, despite it being attempted in seven patients. We conclude that the results of the intestinal rehabilitation program are encouraging for the continuation of this type of treatment and stimulate the creation of the program in other pediatric care institutions.